Deaf culture, our way : anecdotes from the deaf community - Holcomb, Roy K. (DawnSignPress, 2011)
"Using humorous stories with illustrations, this classic collection brings deaf culture to life through personal experiences and practical day-to-day information. Various aspects of the deaf world are illuminated through anecdotes, updated in this edition to include new stories about the foibles of the latest communication technologies, including VRS, videophones, email, and instant messaging. Also provided is classroom material for teachers that can be used as excellent supplemental reading for deaf studies, ASL, or interpreting classes, as well as a springboard for discussions about deaf culture." Amazon.com viewed 5/5/2020.